Implementation of The School-Community Relationship Program Through The Hidden Curriculum During Pandemic - Widiatsih, Asri; Prystiananta, Nostalgianti Citra (JURNAL AL-TANZIM, 2022)
This study aims to describe the implementation of the school-community relationship program through the Hidden Curriculum during the Covid-19 pandemic at Al-Furqan Elementary School Jember. This research focuses on implementing the school-community relationship program through the Hidden Curriculum during the Covid-19 pandemic at Al-Furqan Elementary School Jember. The approach in this research is qualitative research with a case study. The object of research is Al-Furqan Elementary School, Jember Regency. The data collection technique uses observation, interview, and documentation techniques with data analysis using qualitative data analysis procedures consisting of data condensation, data presentation, and inference/verification. The results showed the implementation of the school-community relationship program through the Hidden Curriculum during the Covid-19 pandemic at Al-Furqon Elementary School Jember, including learning, humanitarian, cultural, and partnership programs carried out by; 1) extracurricular activities; 2) co-curricular; and 3) extracurricular. Hidden curriculum through extracurricular activities such as character strengthening, Sunday morning activity, digital literacy, a celebration of religious holidays and the role of school committees. Co-curricular activities implemented are morning habituation with memorizing prayers, fostering homeroom teacher and Counseling Guidance teacher, and reciting the Qur'an, which is carried out through zoom and learning using google classroom. Extracurricular activities are scouting, computers and young doctor, all carried out online.